2019
DOI: 10.1016/j.sigpro.2018.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Iterative marginal maximum likelihood DOD and DOA estimation for MIMO radar in the presence of SIRP clutter

Abstract: The spherically invariant random process (SIRP) clutter model is commonly used in scenarios where the radar clutter cannot be correctly modeled as a Gaussian process. In this short communication, we devise a novel Maximum-Likelihood (ML)-based iterative estimator for direction-of-departure and direction-of-arrival estimation in the Multiple-input multiple-output (MIMO) radar context in the presence of SIRP clutter. The proposed estimator employs a stepwise numerical concentration approach w.r.t. the objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…For estimation of the aforementioned targets' parameters in the non-Gaussian clutter environment, various variants of maximum likelihood estimator (MLE) are proposed in [13], [14], and [15]. However, the estimation of DOD, DOA, and Doppler shift, in the presence of non-Gaussian clutter, does not have a closed-form solution for optimization of MLE cost function [16].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For estimation of the aforementioned targets' parameters in the non-Gaussian clutter environment, various variants of maximum likelihood estimator (MLE) are proposed in [13], [14], and [15]. However, the estimation of DOD, DOA, and Doppler shift, in the presence of non-Gaussian clutter, does not have a closed-form solution for optimization of MLE cost function [16].…”
Section: Introductionmentioning
confidence: 99%
“…The MLE based solution, proposed in [13], and [14] are based on the conditional likelihood, and the joint likelihood of the observations, respectively. Later, in [15], it is mentioned and shown that the estimators proposed in [13], and [14] are prone to yield suboptimum estimates of required parameters. Therefore in [15], an iterative ML estimator has been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations